Clinical Characteristics and Outcomes of Hospitalized AECOPDs Secondary to SARS-CoV-2 versus Other Respiratory Viruses - Chhor L; Saggese S; Hamilton GS; MacDonald MI (International Journal of COPD)
Louis Chhor,1,2 Stefan Saggese,2 Garun S Hamilton,1,3 Martin Ian MacDonald1 1Monash Lung, Sleep, Allergy & Immunology, Monash Health, Melbourne, Victoria, Australia; 2Department of General Medicine, Monash Health, Melbourne, Victoria, Australia; 3School of Clinical Sciences, Monash University, Melbourne, Victoria, AustraliaCorrespondence: Louis Chhor, Department of General Medicine, Dandenong Hospital, 135 David St, Dandenong, VIC, 3175, Australia, Tel +61 3 9544 1000, Email louis.chhor2@easternhealth.org.auObjective: To compare clinical characteristics and outcomes of hospitalized acute exacerbations of COPD (AECOPD)s secondary to SARS-CoV-2 versus other respiratory viruses amongst a highly vaccinated population in the Omicron era.Design: Retrospective cohort study; analysis of hospital medical records and linked pathology and radiology reports.Setting: Tertiary health network in Victoria, Australia; January 2022–August 2022.Main Outcome Measures: Key clinical information including comorbidities, vaccination status, treatments administered and outcomes such as hospital length of stay, ICU admission, non-invasive ventilation usage and inpatient mortality.Results: One hundred ninety-nine viral AECOPDs - 125 SARS-CoV-2 and 74 other viruses were identified. Of the SARS-CoV-2 group. 13.6% were unvaccinated, 17.6% partially and 68.0% fully vaccinated. The SARS-CoV-2 group were older (77.2 vs 68.9, p < 0.00001) with more comorbidities (1[1– 2] vs 1[0– 2], p = 0.008) and lower candidacy for full resuscitation (25.6% vs 56.8%, p < 0.0001). Mortality tended to be higher among SARS-CoV2 admission (9.6% v 2.7%, p = 0.066) but rates of ICU admission (10.4% v 13.5%, p = 0.507), length of hospitalisation (5[3– 8] vs 5[3– 9], p = 0.9) and readmission within 30 days (25% vs 33.3%, p = 0.184) were similar.Conclusion: In a highly vaccinated population in the Omicron era, COPD patients requiring hospitalisation with SARS-CoV-2 are older with more comorbidities than those admitted with other respiratory viruses. Length of hospitalisation and ICU utilisation was similar. Inpatient mortality may be higher.Keywords: SARS-CoV2, coronavirus, COPD, viral exacerbations